Does family confidence bridge child functioning and caregiver burden in early intervention? - Gabriel Martínez-Rico; Pau García-Grau; Margarita Cañadas-Pérez; Rómulo J. González-García (PLoS ONE, 2025)
Background: Enhancing caregivers’ confidence and competence in early childhood intervention is a priority, focusing on collaboration between professionals and families to improve family well-being and quality of life. Caregiver burden is crucial in early childhood intervention support services aimed at promoting family well-being and functioning. However, contextual factors and child-related variables may affect caregiver burden. We examined the relationships between family confidence, caregiver burden, and child functioning. Method: A total of 169 Spanish families receiving early intervention services participated in a cross-sectional survey study. Data were analyzed applying single and multiple mediation analyses to examine the influence of socio-demographic variables on family confidence and caregiver burden, as well as the mediating role of family confidence between child functioning and caregiver burden. Results: The study found that child functioning does not directly impact caregiver burden but significantly influences it through family confidence. Confidence in helping the child was a relevant mediator of the impact of child functioning on caregiver burden. However, confidence in helping the family was a mediator across all dimensions of caregiver burden. Conclusions: Higher family confidence predicts lower caregiver burden in early childhood intervention. Confidence in helping family functioning is key to mitigating the negative impact of child functioning on caregiver burden. Practical implications of these findings suggest that early childhood intervention services should focus on capacity-building through collaborative and family-centered practices, empowering families to enhance their confidence, and reduce caregiver burden.